IMPROVING STUDENTS’ PRONUNCIATION BY USING ENGLISH SONGS FOR FOURTH SEMESTER STUDENTS OF ENGLISH EDUCATION PROGRAM BATANGHARI UNIVERSITY ACADEMIC YEAR 2015/2016 - nurul fitri (Universitas Batanghari Jambi, 2017)
This research is aimed at identifying the effect of using English songs in increasing students’ pronunciation in semester IV program in English Education program Batanghari University Academic Year 2015/2016. The population of this research is 28 students of fourth semester. The population of the research is devided into 14 students of experimental class and 14 students of control class. The experiment class is taught by using English songs technique while control class is taught by using repetition of words or practical technique. This research is experimantal research. The data are taken from pronunciation tests which are given in learning process. The result of the research shows that English songs technique can improve students’ pronunciation. It is concluded from the post-test that there is statistically difference of the mean between experimental class and control class. The mean score of experimental class is 91.78 and the mean score of control class is 84.64. it means that the mean score of experimental class is higher than control class. Post-test also indicates an improvement on students’ pronunciation after the students is taught by English songs technique. There is statistically difference on the result of t-test and t-table in which t-test is bigger than t-table, 2.29 > 2.00.